Large-scaled human serum sphingolipid profiling by using reversed-phase liquid chromatography coupled with dynamic multiple reaction monitoring of mass spectrometry: Method development and application in hepatocellular carcinoma - Li, Jia; Hu, Chunxiu; Zhao, Xinjie; Dai, Weidong; Chen, Shili; Lu, Xin; Xu, Guowang (Journal of Chromatography A, 2013)
•Using tert-butyl methyl ether with mild alkaline hydrolysis for sphingolipid extraction.•UHPLC-dynamic multiple reaction monitoring method for serum sphingolipid profiling.•84 serum endogenous sphingolipids can be detected in a single LC run within 10min. Sphingolipids are a family of bioactive molecules with high structural diversity and complexity. They not only serve as integral components of cellular membrane, but also play pivotal roles in signaling and other cellular events. It is desirable for the development of sensitive, robust and structural-specific analytical approaches enabling rapid determination of as many sphingolipid species as possible. Herein we present an analytical method for large-scaled profiling of sphigolipids in human serum, which consisted of an improved extraction protocol using tert-butyl methyl ether combined with mild alkaline hydrolysis, and an ultra high performance reversed-phase liquid chromatography-dynamic multiple reaction monitoring-mass spectrometric (RPLC-dynamic MRM-MS) method. In total 84 endogenous sphingolipid species covering six subcategories (i.e. free sphingoid base, dihydroceramide, ceramide, hexosylceramide, lactosylceramide, and sphingomyelin), were separated and quantified in a single run within 10min. A broad linear range over 2.5–4 orders of magnitude (r2>0.99), a limit of detection of 0.01–0.17pmol/mL, and a limit of quantitation of 0.02–0.42pmol/mL were obtained for each subcategory. Average recovery of each subcategory was within 85.6–95.6%. Median values of coefficient of variation (CV) of all detected 84 sphingolipids were 3.9% and 6.8% for intraday and interday precision, respectively. This method was exemplarily applied in a study regarding dysregulated sphingolipid homeostasis in hepatocellular carcinoma. The establishment of this method provides a useful tool for serum-based high throughput screening of sphingolipid biomarkers and mechanism investigation of sphingolipid metabolic regulation in human disease.